DEVELOPMENT OF BALANCE INSTRUMENTS FOR CHILDREN 5-6 YEARS OLD - Pranoto, Nuridin Widya (Jurnal Sporta Saintika, 2023)
Balance is one of the motor skills that is important to master from an early age. Having the ability to balance becomes a support for more complex movement abilities that are useful in carrying out movements in everyday life. This study aims to develop a balance instrument that can be used to measure the balance ability level of children aged 5-6 years. The method used in this research is research and development (R&D) using the ADDIE model with procedures (1) analysis (2) design (3) implementation (4) evaluation. A total of 30 children participated in this study with an age range of 4-6 years. Validity and reliability data were tested using SPSS 16. From the results of the study it was obtained (1) a complex balance test instrument for children with an age range of 5-6 years, (2) there were 30 balance test items which were declared valid, the value of r count > r table stating that this instrument is reliable and can be used as a balance measurement tool. Based on the results of the study, it can be concluded that the developed balance instrument can measure the components of balance in children aged 5-6 years.